Selection method is one of the most important factors in determining the success of pepper breeding programs. Selection method will be effective if it is supported by a complete knowledge of genetic character inheritance. The aim of this research was to investigate the inheritance patterns to quantitative characters using large pepper (P1 (IPB C5)), curly pepper (P2 (IPB C105)), F1, F1R, BCP, BCP2 and F2. The result showed that dichotomous height, days to harvest and weight per fruit characters - Arif, Abdullah Bin; Sujiprihati, Sriani; Syukur, Muhamad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
Selection method is one of the most important factors in determining the success of pepper breeding programs. Selection method will be effective if it is supported by a complete knowledge of genetic character inheritance. The aim of this research was to investigate the inheritance patterns to quantitative characters using large pepper (P1 (IPB C5)), curly pepper (P2 (IPB C105)), F1, F1R, BCP, BCP2 and F2. The result showed that dichotomous height, days to harvest and weight per fruit characters were not maternally inherited. The additive-dominant genetic model was the most suitable for dichotomous height character. The additive-dominant with influence of interaction additive-dominant and interaction dominant-dominant genetic model was suitable for days to harvest character. The additive-dominant with influence of interaction additive-additive and interaction dominant-dominant genetic model was suitable for the weight of fruit character. Broad-sense and narrow-sense heritabilities range medium for dichotomous height and weight per fruit characters. Heritability of the days to harvest character was high in a broad-sense but was low in the narrow-sense. Keywords: genetic model, heritability, inheritance